2014
DOI: 10.1002/eat.22286
|View full text |Cite
|
Sign up to set email alerts
|

Testing the measurement invariance of the eating disorder inventory in nonclinical samples of Hispanic and Caucasian women

Abstract: The theoretical three-factor structure of the EDI eat/wt scales was supported in both ethnic groups. Furthermore, the Drive for Thinness scale can readily be used to make group comparisons across nonclinical samples of Caucasian and Hispanic women, but researchers should be cautious when using the other two eat/wt scales to make comparisons across these two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…We examined EDI‐DFT scores as a continuous explicit measure of drive for thinness. Consistent with previous literature (Becker et al, ), individuals with NFP‐AN in our study had significantly lower explicit EDI‐DFT scores than those with FP‐AN, falling within a range similar to that of a nonclinical sample (Belon et al, ). Although explicit EDI‐DFT scores differed between individuals with NFP‐ and FP‐AN, they showed similar implicit biases toward thinness and dieting, which further supports that explicit endorsements do not match implicit attitudes.…”
Section: Discussionsupporting
confidence: 92%
“…We examined EDI‐DFT scores as a continuous explicit measure of drive for thinness. Consistent with previous literature (Becker et al, ), individuals with NFP‐AN in our study had significantly lower explicit EDI‐DFT scores than those with FP‐AN, falling within a range similar to that of a nonclinical sample (Belon et al, ). Although explicit EDI‐DFT scores differed between individuals with NFP‐ and FP‐AN, they showed similar implicit biases toward thinness and dieting, which further supports that explicit endorsements do not match implicit attitudes.…”
Section: Discussionsupporting
confidence: 92%
“…Recent diversity-affirming ED research, therefore, includes norming and reformulation efforts for standardized ED assessments such as the Eating Disorder Inventory and the Eating Disorder Examination-Questionnaire for heterosexual men (56), gay men (57), transgender persons (58,59), and Black patients (60). Although some of these efforts have revealed a convergence of questionnaire structures between diverse samples (61,62), others have shown that identical questionnaires may measure dissimilar constructs in different diverse groups (63), emphasizing the necessity for validation across groups.…”
Section: Updates In Diagnostic Criteriamentioning
confidence: 99%
“…Given that ED presentation was comparable or more severe in WOC than in White women in this study, future efforts must address treatment disparities between minority and non‐minority women with EDs. There are likely multiple factors that contribute to screening and treatment disparities between WOC and non‐Hispanic, White women with EDs, such as mental health stigma (Gary, 2005), clinician bias leading to lower rates of ED identification in WOC (Becker et al, 2003; Goel et al, 2020a), and lack of culturally‐sensitive assessments (Belon et al, 2015). Findings from this study could inform future ED screening to reduce disparities in underrepresented populations, especially with regards to the high endorsements of binge eating in Asian/South Asian women and laxative use and insomnia symptoms in Hispanic women.…”
Section: Discussionmentioning
confidence: 99%